Cohort study of malignancies and hospitalized infectious events in treated and untreated patients with psoriasis and a general population in the United States. (11th October 2015) - Kimball, A.B.; Schenfeld, J.; Accortt, N.A.; Anthony, M.S.; Rothman, K.J.; Pariser, D.
Abstract : What's already known about this topic? Patients with psoriasis appear to have a higher risk of some types of malignancies than the general population, which may be due to underlying disease pathology. Many treatments for psoriasis have immunosuppressive properties, which may contribute to higher risk of infections. What does this study add? This study provides up to 5 years of follow‐up on the risk of malignancy for patients with psoriasis treated with systemic therapies. Most systemic therapies evaluated in this study did not appear to be associated with increased malignancy rates. This study provides rates of hospitalized infectious events across the treatment spectrum, and adds information that may help differentiate the influence of disease vs. treatments for these outcomes. Summary: Background: Psoriasis is associated with risk of malignancy. Some psoriasis treatments may increase the risk of hospitalized infectious events (HIEs). Objectives: To evaluate rates of malignancies and HIEs in patients with psoriasis. Methods: This retrospective cohort study utilized data from MarketScan ® databases. Cohorts included adult general population (GP), patients with psoriasis, and patients with psoriasis treated with nonbiologics, adalimumab, etanercept, infliximab or phototherapy. Outcomes included incidence rates (IRs) per 10 000 person‐years observation (PYO) for all malignancies excluding nonmelanoma skin cancer (NMSC), lymphoma, NMSC, and per 10 000 person‐years of exposure (PYE) for HIEs. Results: Incidence rates [95% confidence interval (CI)] for all malignancies except NMSC were 129 (127–130) and 142 (135–149) for GP (PYO = 51 071 587) and psoriasis (PYO = 119 432) cohorts, respectively; 10·9 (10·5–11·3) and 12·9 (10·9–14·8) for lymphoma; and 145 (144–147) and 180 (173–188) for NMSC. Rates for all malignancies excluding NMSC were similar among treatments but variable for lymphoma and NMSC. IRs (95% CI) for HIEs were 332 (256–408) for the nonbiologic cohort (PYE = 3528); 288 (206–370) for etanercept (PYE = 6563); 325 (196–455) for adalimumab (PYE = 2772); 521 (278–765) for infliximab (PYE = 1058); and 334 (242–427) for phototherapy (PYE = 1797). IRs for HIEs were lowest for etanercept and higher in patients on baseline systemic corticosteroids across treatment cohorts. Conclusions: Malignancy rates were higher in patients with psoriasis than the GP, but these treatments did not appear to increase malignancy risk.